A RADIOLUMINESCENCE STUDY OF DOSE CHARACTERISTICS OF LIF:MG, TI. Issue 2 (2nd August 2021) - Zhang, Siyuan; Tang, Kaiyong; Fan, Haijun; Li, Zhiyuan; Huang, Guangwei; Wu, Kun; Fu, Li
Abstract: A radioluminescence (RL) study of dose characteristics of tissue-equivalent LiF:Mg, Ti was carried out to determine the possible application as a real-time dosemeter. An RL measurements system based on LiF:Mg, Ti coupled with optical fiber was developed, and a blank fiber was set to remove the stem effect generated by the optical fiber due to direct radiation. A slight increase of RL sensitivity with accumulated dose and the afterglow effect due to shallow traps in LiF:Mg, Ti were observed, thus a set of algorithms was adopted to correct measured dose rate. A good linearity of dose-rate response using RL in LiF:Mg, Ti over more than four orders of magnitude (from 0.76 mGy/h to 8.02 Gy/h) was shown, and the deviation of calibrated dose rate is within 20%. Moreover, a satisfactory reproducibility (1.45%) of the measured dose rate after correction was represented. The results indicated that LiF:Mg, Ti might be promising for real-time dose monitoring.